An introduction to islamic finance : theory and practice - Mirakhor, Abbas (Wiley finance, 2011)
Much has happened in the Islamic finance industry since this bestselling text was first published in 2007. This second edition is timely especially as there has been much re-thinking of the role of Islamic banks in the aftermath of the global financial crisis. New chapters on risk-sharing and financial stability, and other revisions should ensure that this remains the leading text in its field, with the strengths of the first edition retained, not least the lucid explanations of often complex financial products helped by useful flow charts. Professor Rodney WilsonDirector, Durham University Is